BOTULINUM TOXIN IN THE TREATMENT OF STRABISMUS: A REVIEW OF THE LITERATURE (2015–2025) - Karolina Nowacka (International Journal of Innovative Technologies in Social Science, 2025)
Background: Botulinum toxin type A (BoNT-A) has become an important minimally invasive tool in the management of strabismus, either as an alternative or as an adjunct to extraocular muscle surgery. Over the last decade, a growing body of evidence has evaluated its efficacy, safety and optimal indications. Purpose: To review current evidence (2015–2025) on the use of botulinum toxin type A in the treatment of strabismus, with a focus on mechanism of action, clinical indications, efficacy, safety profile and its role in modern management algorithms. Methods: Narrative review based on literature published between 2015 and 2025 identified in PubMed, Cochrane Library and major ophthalmology journals. Included were systematic reviews, meta-analyses, randomized controlled trials, observational studies and evidence-based guidelines. Results: BoNT-A is effective in small- and moderate-angle comitant strabismus, infantile esotropia in selected cases, acquired non-accommodative and acute acquired comitant esotropia, paralytic strabismus and residual postoperative deviations. In some indications its outcomes are comparable to surgery, although repeated injections may be required. Adverse events are usually mild and transient, such as ptosis, transient overcorrection and temporary diplopia. Conclusions: BoNT-A is an established and safe option in the management of selected forms of strabismus. Further high-quality clinical trials are needed to standardize dosing protocols, timing of intervention and combined approaches with extraocular muscle surgery.